2023
DOI: 10.1007/s11701-023-01539-5
|View full text |Cite
|
Sign up to set email alerts
|

Robot-assisted radial forearm free flap harvesting: a propensity score-matched case–control study

Abstract: Although some surgeons prefer anterolateral thigh and latissimus dorsi ap for soft tissue reconstruction in head and neck area because it minimizes donor site complications, radial forearm ap remains the workhorse for soft tissue reconstruction due to its reliability. To reduce donor site morbidity, the authors developed a novel technique for radial forearm ap harvesting using a robotic device. 42 radial forearm free ap reconstruction cases were studied, consisting of 31 conventional and 11 robotassisted cases… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
(13 reference statements)
0
2
0
Order By: Relevance
“…In postoperative follow-up, the robot cases had better and superior aesthetic outcomes due to reduced linear scarring. However, the robot-assisted harvesting took significantly longer time than the conventional group 16 .…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In postoperative follow-up, the robot cases had better and superior aesthetic outcomes due to reduced linear scarring. However, the robot-assisted harvesting took significantly longer time than the conventional group 16 .…”
Section: Discussionmentioning
confidence: 94%
“…2), among which one(1.1 %) 14 site haematoma 18 1 (1.1 %), donor site morbidity i.e abdominal hernias or wound healing 15 in 1(1.1 %) and unspecified surgical site occurrences (including breast wound dehiscence, infection, skin flap necrosis, fat necrosis, haematoma and seroma)20 5(5.8%), moreover, complication status was not reported for 41 patients. 16,22,23 Analysis of complications by flap type showed that all these patients had DIEP flap reconstruction, therefore, complication rate in DIEP flap, with denominator 120, was 15(12.5%).…”
Section: Outcomes For Robotic-assisted Flap Harvestmentioning
confidence: 97%